Foliar sprays of citric acid and salicylic acid alter the pattern of root acquisition of some minerals in sweet basil (Ocimum basilicum L.) - Ghazijahani, Noushin; Hadavi, Ebrahim; Jeong, Byoung R. (Frontiers in Plant Science, 2014)
The effect of foliar application of two levels of citric acid (0 and 7 mM) and two levels of salicylic acid (0 and 1mM) combined with two levels of nutrient solution strength (full strength and half strength) on mineral acquisition by sweet basil were investigated. The experiment was conducted in a randomized block design arrangement with three replications. Salicylic acid alone reduced the plant height and thickened the stem. Plants supplied with a full strength solution had a ticker stem, produced more biomass, and showed higher values of Fv/Fm. Some changes in the uptake pattern of some nutrients, especially boron and sulfur, were noticed. Higher boron concentrations in leaves were in plants sprayed with a combination of 7 mM citric acid and 1 mM of salicylic acid. Applying combination of citric acid and salicylic acid was more effective than using them individually that suggests an effective synergism between them.